Establishing the excitation field in tip-enhanced Raman spectroscopy to study nanostructures within two-dimensional systems. (1st January 2023) - Miranda, Hudson; Monken, Vitor; Campos, João Luiz E; Vasconcelos, Thiago L; Rabelo, Cassiano; Archanjo, Bráulio S; Almeida, Clara M; Grieger, Sebastian; Backes, Claudia; Jorio, Ado; Gustavo Cançado, Luiz
Abstract: The optical field generated by a nanoplasmonic probe is revealed in tip-enhanced Raman spectroscopy (TERS) experiments. The TERS intensity profile of nano-objects smaller than the probe's apex has a donut-like shape which resembles the magnitude of the field generated by a point-dipole source, being well described by the Dyadic Green's function. Having prior knowledge on the excitation field generated by the TERS probe, we measured the width of shear solitons caused by lattice reconstruction in low-angle twisted bilayer graphene, a prominent platform for twistronics, and the extend of defect-induced light emission from graphene edges.